The Role of Auditor Characteristics in Key Audit Matters Disclosures: Evidence from Indonesian Listed Manufacturing Companies - Amin, Khairul Insan Al; Handayani, R. R. Sri (Jurnal Dinamika Akuntansi dan Bisnis, 2025)
This study examined the influence of auditor characteristics on Key Audit Matters (KAM) disclosure. The independent variables are audit firm reputation, audit fees, auditor industry specialization, auditor rotation, and audit tenure. The population consists of manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2022 and 2023. The samples were selected using a purposive sampling technique, resulting in 245 firm-year observations. Using multiple linear regression analysis, this study found that audit fees positively affect KAM disclosure, while audit firm reputation, auditor industry specialization, auditor rotation, and audit tenure did not have a significant impact. The findings imply that financial incentives, such as higher audit fees, may encourage auditors to provide more detailed and transparent KAM disclosures.